Water stress versus yield components and quality must (Vitis vinifera L.) cv. Negra Criolla - Díaz, Keith (2016)
The main objective of the current work was to evaluate the effect of irrigation water quantity (IWQ) on yield components and grape must quality of cv. Negra Criolla at Caraveli Valley, Arequipa. Results showed significant differences on grape bunch number (T3 = 57; T2 = 36), berry number per bunch (T0 = 147; T1 = 66), equatorial diameters of berries B1, B2 and B3 (T3 = 13, 14 y 14; T0 = 14, 13 y 13 mm), berry bunch weights (T3 = 10.58; T2 = 7.87 kg.cepa-1) and grape must quality such as density (T2 - T3 = 1.104; T2 = 1.097 g.L-1), pH (T0 = 3.75; T1 = 3.59), and phenol compound content a Gallic acid (T0 = 1.75; T2 - T3 = 1.66 mg.L-1). In conclusion, T3 treatment produced the higher differences, but declining pH, Brix degrees and Gallic acid values.